TOBACCOS ALLY GROUPS HELP GET THE WORD OUT THE LOBBYING ARM OF THE INDUSTRY SHAKES HANDS WITH HUNDREDS OF OTHER GROUPS HERE AND ACROSS THE NATION - GORDON G; HAMBURGER T; HAMILTON C; STEFANY J (Tufts Archival Research Center, 2007)
Article in the Minneapolis Star Tribune reporting on the lobbying efforts of the Tobacco Industry. Points to new strategies which gain support from local firms and other industries and non-profits that would normally not be associated with the tobacco industry and has them lobby on behalf of the industry. Compares the legislators which support the industry to those that do not.